2011
DOI: 10.1007/s00049-011-0090-6
|View full text |Cite
|
Sign up to set email alerts
|

Volatile emissions from the flea beetle Altica litigata (Coleoptera: Chrysomelidae) associated with invasive Ludwigia hexapetala

Abstract: The flea beetle Altica litigata (Chrysomelidae) is an insect herbivore to plants within the families Lythraceae and Onagraceae, including ornamentals such as crape myrtle, Lagerstroemia spp. This insect is important both as a pest species and as a naturally occurring biological control agent due to its aggregate feeding behavior, which typically results in severe defoliation of the host plant. Despite the negative economic impact to ornamentals and contrary benefits as a biological control agent, there are few… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 23 publications
1
8
0
Order By: Relevance
“…This study corroborates that the VOC profiles from plants can vary within the genus Ludwigia (Carruthers et al, 2011;Roitman et al, 2011;Mukherjee et al, 2015;Sarkar et al, 2016). Carruthers et al (2011) reported that profiles of VOCs in subspecies of Ludwigia peploides (Kunth) PH Raven ssp. peploides and montevidensis were similar, and among the eight sesquiterpenes, a-copaene, c-muurolene, and d-cadinene were predominant in both subspecies.…”
Section: Discussionsupporting
confidence: 89%
“…This study corroborates that the VOC profiles from plants can vary within the genus Ludwigia (Carruthers et al, 2011;Roitman et al, 2011;Mukherjee et al, 2015;Sarkar et al, 2016). Carruthers et al (2011) reported that profiles of VOCs in subspecies of Ludwigia peploides (Kunth) PH Raven ssp. peploides and montevidensis were similar, and among the eight sesquiterpenes, a-copaene, c-muurolene, and d-cadinene were predominant in both subspecies.…”
Section: Discussionsupporting
confidence: 89%
“…There are also many morphological synapomorphies for all of the Onagraceae except Ludwigia (Levin et al ., ). In France, the herkogamous flowers are intensely visited by many insect pollinators so Ludwigia may also contain potential attractants for some insects (Carruthers et al ., ). For example, in California L. peploides produces and emits a total of eight sesquiterpenes, and L. grandiflora provides a number of monoterpenes in relatively large quantities in addition to several sesquiterpenes in lower amounts (Carruthers et al ., ).…”
Section: Biologymentioning
confidence: 97%
“…For instance, our laboratories have utilised SPME fibres for the collection of static headspace volatiles from plant parts enclosed in customised Teflon® bags as well as purge and trap systems with Tenax® to: analyse host‐plant volatiles for potential attractants for the insect pest navel orangeworm (Beck et al ., , ); determine host‐plant volatile emissions from the invasive weed Ludwigia spp. as well as the insect emissions of a potential biocontrol agent Altica litigata (Carruthers et al ., ); and to evaluate possible chemotaxonomical volatiles from several invasive weeds (Beck et al ., ; Smith and Beck, ). As mentioned above, there are a number of instruments and detectors available for volatile analyses; however, the most commonly employed is the bench‐top GC–MS, which has acceptable detection capabilities for most applications.…”
Section: Collection Of Plant Volatilesmentioning
confidence: 99%